PREVENTING SUBSTANCE ABUSE AMONG ADOLESCENTS: EVALUATION OF AN INTEGRATED MODEL COMBINING LIFE SKILLS TRANING AND PARENT TRANING - Moon, Sung Seek; Kim, Yi Jin; Jang, S. Mo; Yoon, Seokwon; Kim, Jeongsuk (PEOPLE: International Journal of Social Sciences, 2016)
This study examines the effectiveness of an integrated model combining Life Skills Training (LST) for students and Love and Logic Training (LLT) for parents. 310 middle school students and 49 parents were participated in the study. A paired sample t-test was computed to compare pre and post-test scores for each participant. An independent sample t-test was used to determine if statistical differences exist between the treatment and control groups. Alcohol use and resistance to alcohol use among both treatment and control groups were significantly changed after the intervention in a positive way. No significant change in substance use was found in both groups. When it comes to comparison between treatment and control groups, a significant difference was found only in resistance to alcohol use, meaning participants in treatment group showed significantly higher level of resistance to alcohol use than control group after the intervention. Implications of these results for practice and training were discussed.